脂肪酶位置选择性的影响因素Factors affecting the regioselectivity of lipase - 康佳惠子1,2，王秀秀2，贾敏2，徐同成1,2，宗爱珍2,杜方岭2，黄凤洪2，尤艳莉1 KANG Jiahuizi1,2, WANG Xiuxiu2, JIA Min2, XU Tongcheng1,2， ZONG Aizhen2, DU Fangling2， HUANG Fenghong2， YOU Yanli1 (Zhongguo youzhi, 2023)
为开发高效、绿色、低成本的脂肪酶应用于结构脂质的制备，从内源性（脂肪酶的来源、基因序列、空间位阻）和外源性(底物空间结构、反应介质、固定化条件及反应pH)两方面讨论了脂肪酶位置选择性的影响因素。脂肪酶催化特异性由内源性因素和外源性因素共同决定。改变底物空间结构、反应介质、固定化条件和反应pH，常被用作提高脂肪酶催化性能的处理方式。只有充分考虑内外两方面因素的影响，才能充分提高脂肪酶的位置选择性和催化效率。该综述有望为高选择性脂肪酶的开发开辟新的研究方向，为后续结构脂质的高效合成提供启发性的研究思路。 To develop efficient, green and low-cost lipases for the preparation of structured lipid, the factors affecting lipase regioselectivity were discussed in terms of both endogenous (source of lipase, gene sequence, spatial resistance) and exogenous (substrate spatial structure, reaction medium, immobilization conditions and reaction pH). The lipases catalytic specificity were determined by the endogenous and exogenous factors, and changing the substrate spatial structure, reaction medium, immobilization conditions and reaction pH, were often used as treatment ways to improve the catalytic performance of the lipase. Only by fully considering the effects of both internal and external factors, the regioselectivity and catalytic efficiency could be improved. The summarize is expected to develop new research directions for the development of highly selective lipase and provide enlightening research ideas for the subsequent efficient synthesis of structured lipid.